Functionalized BODIPY derivatives as potential fluorescent labels - Gonçalves, R. C. R (2018)
BODIPY derivatives 1 and 2 were obtained with 16 % and 33 % yield by a two-step reaction: condensation of a pyrrole with the corresponding aldehyde followed by oxidation with DDQ in the presence of BF3OEt2. The two compounds were characterized by the usual spectroscopic techniques and a detailed photophysical study was undertaken. The compounds exhibited intense absorption bands at 502 nm and 497 nm, respectively. Emission studies of the compounds 1 and 2 showed emission bands with maximum wavelength at 518 nm and 519 nm, respectively.